2012
DOI: 10.1007/s10709-012-9675-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of Cydia pomonella (Lepidoptera: Tortricidae) populations with different levels of sensitivity towards the Cydia pomonella granulovirus (CpGV)

Abstract: Microsatellite (simple sequence repeats, SSR) and mitochondrial DNA markers were used to assess the structure of European codling moth populations showing different levels of susceptibility towards one of the most important biocontrol agents used in apple production, the Cydia pomonella granulovirus CpGV-M. In 638 C. pomonella individuals from 33 different populations a total of 92 different alleles were scored using six SSR loci. The global estimate of genetic differentiation for all 33 populations was not si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Microsatellites are popular genetic markers because of their co-dominance, high abundance and polymorphism rates, multi-allelic nature, and rapid detection of alleles by a wide variety of methods (Queller et al ., 1993 ; Ellegren, 2004 ; Choudhary et al ., 2009 ; Dutta et al ., 2011 ; Duan et al ., 2014 b ). In recent years, SSR markers have been increasingly widely used in genetic variation studies of insect populations (Behura, 2006 ), such as genetic variation, genetic diversity and phylogenetic relationship analyses of silkworm ( Bombyx mori ) (Li et al ., 2005 a , b ), Mediterranean fruit fly ( Ceratitis capitata ) (Bonizzoni et al ., 2001 ), bumble bee ( Bombus hypnorum ) (Paxton et al ., 2001 ), Argentine ant ( Linepithema humile ) (Tsutsui et al ., 2003 ), wild silkworm ( Bombyx mandarin ) (Li et al , 2005 a ), Cacopsylla chinensis Yang et Li (Sun et al ., 2011 ), biotype Q whitefly ( Bemisia tabaci Gennadius) (Tsagkarakou et al ., 2012 ), brown planthopper ( Nilaparvata lugens Stål) (Jing et al ., 2012 ), Cydia pomonella L. (Gund et al ., 2012 ), silkmoth ( Antheraea assamensis Helfer) (Singh et al ., 2012 ), fall armyworm ( Spodoptera frugiperda ) (Pavinato et al ., 2013 ) and soybean aphid ( Aphis glycines Matsumura) populations (Jun et al ., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellites are popular genetic markers because of their co-dominance, high abundance and polymorphism rates, multi-allelic nature, and rapid detection of alleles by a wide variety of methods (Queller et al ., 1993 ; Ellegren, 2004 ; Choudhary et al ., 2009 ; Dutta et al ., 2011 ; Duan et al ., 2014 b ). In recent years, SSR markers have been increasingly widely used in genetic variation studies of insect populations (Behura, 2006 ), such as genetic variation, genetic diversity and phylogenetic relationship analyses of silkworm ( Bombyx mori ) (Li et al ., 2005 a , b ), Mediterranean fruit fly ( Ceratitis capitata ) (Bonizzoni et al ., 2001 ), bumble bee ( Bombus hypnorum ) (Paxton et al ., 2001 ), Argentine ant ( Linepithema humile ) (Tsutsui et al ., 2003 ), wild silkworm ( Bombyx mandarin ) (Li et al , 2005 a ), Cacopsylla chinensis Yang et Li (Sun et al ., 2011 ), biotype Q whitefly ( Bemisia tabaci Gennadius) (Tsagkarakou et al ., 2012 ), brown planthopper ( Nilaparvata lugens Stål) (Jing et al ., 2012 ), Cydia pomonella L. (Gund et al ., 2012 ), silkmoth ( Antheraea assamensis Helfer) (Singh et al ., 2012 ), fall armyworm ( Spodoptera frugiperda ) (Pavinato et al ., 2013 ) and soybean aphid ( Aphis glycines Matsumura) populations (Jun et al ., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these field populations were 1,000 to 100,000 times less susceptible to CpGV-M than were typical susceptible larvae (13). When 33 resistant and nonresistant CM populations from different geographic origins were analyzed by using microsatellite (simple sequence repeats [SSR]) and mitochondrial DNA markers, it was found that these populations did not differ significantly from each other, and genetic differentiation between resistant and nonresistant populations was not possible (18). This study argued for an independent emergence of resistance at different locations within a very short time.…”
mentioning
confidence: 99%
“…This is a possibility that should also be investigated for other baculovirus-host systems. For example, similar differences have been recorded in the laboratory for both virulence of different CpGV genomes [ 78 ] and susceptibility of different C. pomonella populations [ 79 ].…”
Section: Discussionmentioning
confidence: 56%